2017
DOI: 10.1007/jhep01(2017)023
|View full text |Cite
|
Sign up to set email alerts
|

D = 3 unification of curious supergravities

Abstract: We consider the dimensional reduction to D = 3 of four maximal-rank supergravities which preserve minimal supersymmetry in D = 11, 7, 5 and 4. Such "curious" theories were investigated some time ago, and the four-dimensional one corresponds to an N = 1 supergravity with 7 chiral multiplets spanning the seven-disk manifold. Recently, this latter theory provided cosmological models for α-attractors, which are based on the disk geometry with possible restrictions on the parameter α. A unified picture emerges in D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…which generate SU (2) L when applied to (39). Here, the T j are defined as in equation (35). Finally, the twelfth generator is realised as…”
Section: One Generation As Minimal Idealsmentioning
confidence: 99%
See 1 more Smart Citation
“…which generate SU (2) L when applied to (39). Here, the T j are defined as in equation (35). Finally, the twelfth generator is realised as…”
Section: One Generation As Minimal Idealsmentioning
confidence: 99%
“…It is hoped that these results will be of direct use to those currently working on grand unified theories [12][13][14][15][16][17][18][19], extra dimensions [20][21][22][23][24], and non-commutative geometry [25][26][27][28][29]. Furthermore, it may lend helpful clues to those working in related fields such as supersymmetry [30][31][32][33][34][35][36], and other topics closely related to the division algebras [37][38][39][40]. Finally, the possibility of an extra B−L symmetry mentioned here is particularly exciting given the recent findings of [41][42][43][44].…”
Section: Introductionmentioning
confidence: 98%
“…In this way, the corresponding entropy functions have been computed using the duality symmetries which act on the invariant black object charges. Considering Dbrane physics, several compactfications producing some black brane solutions embedded in type II superstrings have been studied [6,7,8]. It has been shown that these black objects can be linked to many subjects including quantum information theory by exploiting the qubit mathematical formalism [9,10,11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The black objects, embedded in superstring theory compactifications, can be connected to quantum information theory using the qubit analysis [12][13][14][15][16][17][18][19][20][21][22][23][24]. Precisely, a fascinating correspondence has been discovered between quantum information theory and superstring theory.…”
mentioning
confidence: 99%
“…The underlying idea is a link between the N = 2 STU black hole charges and three-qubit states which has been established in [15,16]. Furthermore, the analysis based on three-qubits has been developed to describe the structure of extremal black hole solutions in terms of four-qubit systems [12,19,22,23,28]. In all the works on four-qubits, one uses the complex geometry to deal with the corresponding black hole entropy.…”
mentioning
confidence: 99%